Timing and implications of aeolian sand accumulation in a alpine basin of Qilian Shan, NE Tibetan Plateau - Yang, Na; Zhang, Jingran; Cai, Yun; Feng, Yuye; Yang, Linhai; Cheng, Hongyi; Long, Hao (Frontiers in Earth Science, 2022)
The reconstruction of regional moisture and climate changes during the Holocene has been intensively carried out over the NE Tibetan Plateau, based on different geological archives. However, owing to either the lack of robust independent chronology or ambiguous interpreting of climate proxies as well as complex geographic settings within the plateau, the nature of Holocene environmental changes and their influence factors remain controversial, particularly on whether the optimal climate condition (effective moisture peak) has prevailed during the early- or mid-Holocene. In this study, we reported a new well-dated sand dune accumulation record from the Shawotou sand field in the Babao River drainage area in the southeast Qilian Mountains, to unravel the late glacial and Holocene moisture variation history. The robust chronologies of aeolian sands and palaeosols from two sections were established based on densely collected 49 samples using post-infrared (IR) IR-stimulated luminescence dating of coarse-grained K-feldspar. Based on stratigraphic investigation of the sand dune/palaeosol sections, the results show that the climatic condition was very dry during the late glacial and early Holocene (14–8 ka), characterized by sand dune formation, and then the moisture peaked in the middle Holocene (8–4 ka) with the strongest pedogenesis, followed by a relatively dry condition in the late Holocene (since 4 ka). The regional comparison suggested that the Holocene moisture variation pattern seems synchronous over the NE Tibetan Plateau, that is, the dry early Holocene and late Holocene but with peaked moisture in the middle Holocene, which is likely attributed to the precipitation changes of the East Asian summer monsoon.